Sosial Ekonomi, Literasi Keuangan Digital, Inklusi Keuangan Terhadap Perilaku dan Perencanaan Menabung di Masa Depan - Cahyani, Rifat; Abdurrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Along with the development of the times and technology today, there is a shift in the treatment of conducting financial transactions. This study is a quantitative research using the Structural Equation Model (SEM) method. In socio-economic research with digital financial literacy, saving behavior and future savings planning have a positive influence. Gaps are shown in financial inclusion and digital financial literacy which have no influence on spending planning. In practice, individuals will continue to make their e penses and other factors, namely une pected needs. A positive influence is held between spending planning and saving behavior. However, there is a negative influence between spending planning and future savings planning. Some of the things that can be a factor in the absence of future savings preparation are procrastination and compulsive buying behavior. Positive influence of saving behavior and future savings planning which aims as savings with transactional purposes.